Loop‐shaped elements for anchoring carbon reinforcement in concrete. Issue 4 (15th September 2020) - Speck, Kerstin; Rittner, Steffen; Bracklow, Franz; Ewertowski, Mateusz; Curbach, Manfred; Cherif, Chokri
Abstract: Carbon reinforcements enjoy increasing popularity both in building reinforcement and in new construction. The use of yarns with more than 50 000 filaments per roving and finenesses of up to 3300 tex, so‐called heavy tows, enables greater permissible stress and thus increases the performance of the textile reinforced concrete structures. However, high yarn tensile forces with an almost constant roving surface lead to an extension of the required end anchorage and overlap areas. In the project, it was investigated whether a modified loop‐shaped yarn arrangement at the selvages could guarantee force transmission over shorter lengths and thus enables a more economic design of this type of construction. This paper presents the results generated within the investigations, proving the potential of the applied method. Manufacturing possibilities, force transmission mechanisms, material properties, and failure mechanisms were analyzed.